2018
DOI: 10.1038/s41586-018-0215-y
|View full text |Cite|
|
Sign up to set email alerts
|

Cryo-EM structure of human rhodopsin bound to an inhibitory G protein

Abstract: G-protein-coupled receptors comprise the largest family of mammalian transmembrane receptors. They mediate numerous cellular pathways by coupling with downstream signalling transducers, including the hetrotrimeric G proteins G (stimulatory) and G (inhibitory) and several arrestin proteins. The structural mechanisms that define how G-protein-coupled receptors selectively couple to a specific type of G protein or arrestin remain unknown. Here, using cryo-electron microscopy, we show that the major interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
232
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(263 citation statements)
references
References 67 publications
28
232
2
1
Order By: Relevance
“…(B)]. These polar interactions, noted as “capping interactions”, serve as one of the distinguished features for GPCR‐Gi or ‐Go coupling, are not observed in GPCR–Gs complexes …”
Section: Gpcr–g Protein Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…(B)]. These polar interactions, noted as “capping interactions”, serve as one of the distinguished features for GPCR‐Gi or ‐Go coupling, are not observed in GPCR–Gs complexes …”
Section: Gpcr–g Protein Interactionmentioning
confidence: 99%
“…The conformational differences in TM6 helices of Gi‐ or Gs‐coupling GPCRs have been verified by all‐atom mollified adaptive biasing potential (mABP) simulation. The biased simulations indicated that the intracellular ends of TM6 helices of Gi‐coupling rhodopsin and μOR were considerably less dynamic and remained in a more straight conformation, whereas those of Gs‐coupling β2AR and A 2A R favored an outward tilted conformation …”
Section: Gpcr–g Protein Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four papers in this issue report structures of G i/o -bound GPCRs obtained using cryoelectron microscopy: Koehl et al 2 (page 547) report the structure of the µ-opioid receptor bound to G i1 ; Draper-Joyce et al 3 (page 559) describe the adenosine A 1 receptor in complex with G i2 ; García-Nafría et al 4 (page 620) report the 5HT 1B receptor bound to G o ; and Kang et al 5 (page 553) reveal the structure of the light receptor rhodopsin in complex with G i1 . The G-protein activation cycle involves the binding and release of nucleotides to and from the G proteins, and all of the reported structures capture the receptors bound to the nucleotidefree state of their respective G proteins.…”
mentioning
confidence: 99%
“…GPCRs span the cell membrane and convert myriad extra cellular signals, including neurotransmitter molecules, hormones, and even light, into a cellular response by activating cellular G proteins and other transducer proteins. Four papers [2][3][4][5] in this issue help to unravel the mystery of how GPCRs selectively activate a particular group of G proteins known as G i/o , and provide clues that might aid the design of improved GPCR-targeting drugs.…”
mentioning
confidence: 99%